Streptokinase and Urokinase in the Treatment of Pulmonary Thromboemboli - Bell, William R (Thrombosis and Haemostasis, 1976)
In Phase I of this study of 160 patients with pulmonary embolism, it was demonstrated that 12 hours of urokinase accelerated the resolution of pulmonary thromboemboli compared to heparin alone. Phase II compared 12 hours of urokinase, 24 hours of urokinase and 24 hours of streptokinase in 167 patients. All patients had a clinical history and angiographic diagnosis of pulmonary embolism. Patients were randomly allocated to treatment. All physicians making patient observations were unaware of drug assignment.Resolution of the thromboembolism 24–30 hours after therapy had been instituted was determined by pulmonary angiography, lung perfusion scans and cardiopulmonary hemodynamics. Twenty-four hours of urokinase did not demonstrate greater clot resolution than 12 hours of urokinase. Twenty-four hours of urokinase resulted in greater improvement than streptokinase in lung perfusion scans, but not in angiograms. In patients with massive embolism, this difference was statistically significant. Hemodynamic differences varied.Bleeding complications and morbidity due to allergic reactions with streptokinase and urokinase were minimal. There was no statistically significant difference in mortality in the three treatment groups.From the Phase I and Phase II data it is reasonable to conclude that all three regimens of thrombolytic therapy are more effective than heparin alone in accelerating resolution of pulmonary emboli. Thrombolytic therapy offers the clinician an alternative to pulmonary embolectomy.